1989
DOI: 10.1063/1.344228
|View full text |Cite
|
Sign up to set email alerts
|

Reactive–fast-atom beam etching of GaAs using Cl2 gas

Abstract: GaAs dry etching using reactive–fast-atom beam etching to obtain an etched mirrorlike surface is investigated. An etch rate of 0.1–0.6 μm/min is obtained when Cl2 gas is used, which is 50–100 times faster than when Ar gas is used. The etch rate ratio between GaAs and photoresist AZ-1350J is more than 30. As a result, a trench with a depth of more than 10 μm and a width of less than 2 μm is easily fabricated under the etch conditions of a Cl2 gas pressure of 5–6.5×10−2 Pa, an accelerate voltage of 1.5–1.8 kV, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Anisotropic etching of semiconductors ͑Si, GaAs͒ with a supersonic beam of neutral Cl 2 molecules has been demonstrated. [7][8][9] In addition, work from the space environmental effects community has shown that a beam of energetic oxygen atoms can etch 0.3-m-wide features in an organic polymer with insignificant undercutting. 11 An observation common to both types of etching is the existence of a dependence of the etch rate on initial collision energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic etching of semiconductors ͑Si, GaAs͒ with a supersonic beam of neutral Cl 2 molecules has been demonstrated. [7][8][9] In addition, work from the space environmental effects community has shown that a beam of energetic oxygen atoms can etch 0.3-m-wide features in an organic polymer with insignificant undercutting. 11 An observation common to both types of etching is the existence of a dependence of the etch rate on initial collision energy.…”
Section: Introductionmentioning
confidence: 99%
“…A technique is needed not only to accelerate neutral halogen species to these kinetic energies but also to generate a collimated beam of these species over an area that would permit fabrication of a real chip ͑Ͼ5 cm 2 ͒. Conventional supersonic and effusive beam techniques, [7][8][9] as well as a laser blow-off technique, 15 have been used to study the interaction of neutral species with semiconductor surfaces. Although these experiments reveal much about the interaction mechanisms under the conditions they are studied, the practical range of incident kinetic energies is limited to a few electron volts or less, and the combination of energy and incident flux usually results in too low an etch rate for a study of etch profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the technological importance of these processes, many studies (only some of which are listed here) have looked at how ion beams and plasmas (32)(33)(34)(35)(36)(37), as well as the individual constituents of plasmas [e.g. ions , atoms (38)(39)(40)(41), radicals (26,(42)(43)(44)(45), hot molecules (46,47), electrons (48)(49)(50)(51)(52)(53)(54)(55), and photons (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)], act to etch semiconductor substrates.…”
Section: Introductionmentioning
confidence: 99%
“…A laser diode integrated with a horizontal focusing lens is fabricated by the RIBE method on a GaAs/AlGaAs ( h = 830 nm) etched mirror LD [6] in order to examine the effect of lens fabrication on LD characteristics and the focusing characteristics of the LD beam. An SEM photograph of the fabricated device is shown in Fig.…”
Section: Laser Diode With Horizontal Focusing Lensmentioning
confidence: 99%